A survey of prepollex and prehallux variation in anuran limbs - Fabrezi, Marissa (2001)
This paper reviews skeletal variation of the prepollex and prehallux among anurans and analyses their ontogeny in neotropical species. Morphological diversity is related to the number and features of distal elements. In some groups, clear phylogenetic trends may be interpreted from prepollical and/or prehallical reduction. However, specialized patterns converge from similar habit or behaviour. Developmental data are considered for discussing homology hypotheses and also to interpret evolutionary changes of anuran prepollex and prehallux morphologies. There is an apparent invariance in the presence of these structures that suggests the prepollex and prehallux were integrated, conserved and evolved in the plan of anuran limbs. © 2001 The Linnean Society of London.